The world most oppressed community, Rohingya - U Tun Aung, Maulana Akbar Shah (2017)
The world most oppressed community called Rohingya, who has been struggling to attain self -identity for hundreds of years, yet the success is far from reality. In addition, a new wave of violence in the beginning of 2012 and in July, 2017 intensifies their suffering leading to the exodus of thousands of them to Bangladesh where more than 600.000 Rohingya have started their new lives as refugee in a foreign land. Generally, many observers extend their views on the situation as religious confrontation between the native Rakhine Buddhists and the Muslim Rohingya. Nevertheless, several renowned researchers and information received form internal as well as external sources reveal that the actual problems are basically associated to politico- economic complexity of Myanmar. World media reported that military is behind the whole game and it is also fingered by regional powers such as China, India and the West. The tension between the Buddhists and Rohingya in Myanmar during the military government (1962-2012) was not at the widespread level, but violence against Rohingya deepens when NLD government led by Aung San Su Kyi won the election in 2015. Some comments within Myanmar said that the rule of NLD is assumed to be partial because the military is still holding the ministry of defense, home affair and border region. Since Rohingya lives at the border of Bangladesh, it is the military who is solely responsible for violence and persecution of Rohingya as the UN, US and European community affirmed that the military of Myanmar has committed ethnic cleansing against Rohingya.